Physics of Ce3+↔Ce4+ electronic transition in phytosynthesized CeO2/CePO4 nanocomposites and its antibacterial activities. (January 2021) - Noor, M.; Al Mamun, M.A.; Atique Ullah, A.K.M.; Matsuda, A.; Kawamura, G.; Hakim, M.A.; Islam, M.F.; Matin, M.A.
Abstract: The interplay between physics and chemistry of nanoparticles dictate many useful properties for their practical applications. In this context, we synthesized well controlled CeO2 /CePO4 nanocomposites using Artocarpus heterophyllus aqueous leaf extract as reducing agent. The as-synthesized nanocomposites were annealed at elevated temperatures (500–900 °C) for 3 h under air atmosphere and their characterizations were performed using X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Differential Scanning Calorimetry (DSC) –Thermo Gravimetric (TG) analysis, Raman, Fourier Transform Infrared (FTIR) and UV–Visible spectroscopy analysis. The formation of the CeO2 /CePO4 nanocomposites could be realized by the presence of phosphate ions in aqueous leaf extract which has been confirmed by Gas Chromatography – Mass Spectrometry (GC-MS) analysis. Such stabilization of Ce 3+ ions as CePO4 phase on the surface of nanoceria induced the reduction of grain growth and lowering of the bandgap of the nanocomposites. The antibacterial efficacy against both gram positive ( S. aureus and B. cereus ) and gram negative ( S. typhimurium and E. coli ) bacteria is attributed to the redox cycling between Ce 3+ and Ce 4+ ions at the oxide-phosphate interface of CeO2 /CePO4 nanocomposites. The cytotoxicity analysis observed on two mammalian cell lines (HeLa and Vero) shows that the functional nanocomposites were non–toxic up to higher concentration (3 g/L). Our findings have implication that the phyto-synthesized CeO2 /CePO4 nanocomposites could provide novel insights for mimicking multienzymes' activities and safe for antibacterial applications in terms of in vitro cytotoxicity. Graphical abstract: Fig . (a) Schematic representation of CeO2 –CePO4 nanocomposites and (b) Comparison between the "zone of inhibition" values for 5–15 μL solution of phyto–synthesized CeO2 /CePO4 nanocomposites (500 °C annealed) having concentration of 0.1 g/L against various bacteria. Image 1 Highlights: Stabilization of Ce 3+ as CePO4 phase on the surface of CeO2 /CePO4 nanocomposites via green synthesis. Excellent antibacterial efficacy observed against both gram positive and gram negative bacteria. Insignificant cytotoxicity observed on two mammalian cell lines up to moderately high concentration of nanocomposites.